Donor's therapeutic hypothermia vs. normothermia in kidney transplantation: a meta-analysis of randomized controlled trials - Marcolin Miranda, Luccas; De Lima, Pedro Emanuel Carneiro; Dias Miranda, Nathalia De Carvalho; Margraf, Giovanna Zaniolo; Riella, Juliano (Frontiers in Transplantation, 2025)
IntroductionThe shortage of organs remains one of the most challenging global problems nowadays. Donor's therapeutic hypothermia was suggested to decrease kidney delayed graft function (DGF) when compared to normothermia in previous trials, but the role of such intervention is still controversial. To assess this, we performed a systematic review and meta-analysis of randomized clinical trials (RCTs) investigating the benefits of donor hypothermia in DGF rate and Graft Failure.MethodsMEDLINE, Embase, and Cochrane databases were systematically searched for studies of deceased organ donors who underwent hypothermia or normothermia prior to kidney transplantation. Statistical analysis was performed using R Studio version 3.6. Heterogeneity was assessed using I2 statistics and a Baujat Plot.ResultsFour different RCTs were analyzed, including more than 3,000 recipients. Donor hypothermia was associated with a lower, but not statistically significant, rate of DGF (RR 0.87; 95% CI 0.71–1.08; P = .21) and graft failure (RR 0.70; 95% CI 0.45–1.10; P = .12). When analyzing only expanded criteria donors, a significantly lower rate of DGF was observed in the hypothermia-treated group (RR 0.65; 95% CI 0.47–0.89; P = .008). Sensitivity analysis identified one study as an outlier, probably due to protocol deviation. When excluded from the analysis, a significant reduction in DGF rate was observed among the hypothermia-treated group (RR 0.80; 95% CI 0.67–0.94; P = .007).ConclusionOur meta-analysis could not find a statistical difference between donor therapeutic hypothermia and normothermia in preventing DGF or Graft Failure. However, these results may be influenced by outliers and the limitations of the included studies. Further research is needed to clarify the role of donor hypothermia in kidney transplantation. If proven beneficial, it could be a promising alternative to sites where preservation techniques are limited, such as low-income countries.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024581665, PROSPERO (CRD42024581665).